2023
DOI: 10.3390/ijms24021478
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Landscape of Tea Circular RNAs and Its Contribution to Chilling Tolerance of Tea Plant

Abstract: Chilling stress threatens the yield and distribution pattern of global crops, including the tea plant (Camellia sinensis), one of the most important cash crops around the world. Circular RNA (circRNA) plays roles in regulating plant growth and biotic/abiotic stress responses. Understanding the evolutionary characteristics of circRNA and its feedbacks to chilling stress in the tea plant will help to elucidate the vital roles of circRNAs. In the current report, we systematically identified 2702 high-confidence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…27 At the same time, tea is a major cash crop, and its processing, cultivation, and trade hold substantial economic importance. 28 In this study, we identified a theobromine synthase gene, CsTbS (novel-G000134, Figure S1), and a MYB transcription factor, CsMYB114 (CSS0026328, Figure S2), by correlation analysis of extensively targeted metabolomic and transcriptomic data. The regulatory relationship between CsMYB114 and CsTbS was investigated by using a dual-luciferase reporter gene assay, electrophoretic mobility shift, and yeast one-hybridization techniques.…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…27 At the same time, tea is a major cash crop, and its processing, cultivation, and trade hold substantial economic importance. 28 In this study, we identified a theobromine synthase gene, CsTbS (novel-G000134, Figure S1), and a MYB transcription factor, CsMYB114 (CSS0026328, Figure S2), by correlation analysis of extensively targeted metabolomic and transcriptomic data. The regulatory relationship between CsMYB114 and CsTbS was investigated by using a dual-luciferase reporter gene assay, electrophoretic mobility shift, and yeast one-hybridization techniques.…”
Section: ■ Introductionmentioning
confidence: 94%
“…Its global popularity stems from its health benefits, including antioxidant properties, cardiovascular disease prevention, and potential cancer-fighting ability . At the same time, tea is a major cash crop, and its processing, cultivation, and trade hold substantial economic importance . In this study, we identified a theobromine synthase gene, CsTbS (novel-G000134, Figure S1), and a MYB transcription factor, CsMYB114 (CSS0026328, Figure S2), by correlation analysis of extensively targeted metabolomic and transcriptomic data.…”
Section: Introductionmentioning
confidence: 97%
“…Of them, miR156, miR159, and miR396 showed distinct expression patterns among different cold-sensitive tea varieties under cold conditions ( Zhang et al., 2014b ). In addition, 14 circular RNAs have been identified to contribute to the chilling tolerance of tea plant ( Huang et al., 2023 ).…”
Section: Regulatory Mechanisms Of Cold Tolerance Of Tea Plantsmentioning
confidence: 99%
“…Sci. 2024, 25, 2171 2 of 19 stress in Ammopiptanthus nanus [13], the development of embryos via a lncRNA-miRNA-mRNA network in Picea glauca [14], the regulation of floral development in Glycine max via a circRNA-miRNA-mRNA network [15], and the contribution of a circRNA-miRNA-mRNA network to cold tolerance in Camellia sinensis [16]. As the most important genetic and improvement targets, growth traits have long been the focus of forest researchers to produce more forest products and increase economic benefits.…”
Section: Introductionmentioning
confidence: 99%